Ethics of chicken husbandry: a philosophical and bioethical analysis of cleanliness and cage design - Maftuh Alqadri Zega; Yohana Lasria Siahaan; Marisita Klakik; Nurbaity Situmorang; Mhd Yusuf Nasution (EduMatika: Jurnal MIPA, 2026)
This study aims to analyze the cleanliness and design of laying hen cages and their relationship to disease prevention and livestock welfare from an ethical and bioethical perspective. The method used was a descriptive study with direct observation and interviews conducted at a laying hen farm in Simalungun Regency, North Sumatra. Observed aspects included cage height, distance between chickens and manure, manure removal system, ventilation, and general cleanliness of the cage. The results showed that the cage conditions generally met good standards, with a cage height of approximately 2.5 meters, natural ventilation supporting air circulation, and cage cleanliness maintained through routine cleaning every three days. Adequate distance between chickens and manure and a low fly presence also indicated a relatively low risk of disease transmission. Furthermore, regular use of disinfectants helped control pathogenic microorganisms. From an ethical and bioethical perspective, the husbandry practices implemented reflect the farmer's moral responsibility to maintain animal welfare by providing a clean, healthy, and appropriate environment. However, this study is still limited to a single location and is descriptive in nature, so further research with a broader scope and a quantitative approach is needed.